CONCEPT AND PREVALENCE OF HELICOBACTER PYLORI INFECTION - Khudayberganova N.Kh; Alikulov I.T; Khaitimbetov Zh.Sh; Narziev N.M. (Western European Studies, 2025)
Helicobacter pylori (Hp) bacterium, the etiopathogenetic agent of a number of "gastric" diseases, including stomach cancer, and "extragastric" diseases, affects more than 50% of the world's population. The duration of the evolution of this microorganism in the human population is more than 100 thousand years. The modern epidemic process of Hp infection is characterized by three patterns: 1) age-dependent nature of infection of the population; 2) a slow process of spontaneous release of the population from infection; 3) reinfection of part of the recovered population. The resultant of these processes leads to a gradual decrease in the infection rate of the population in developed countries. In developing countries, there is a consistently high infection rate and high incidence of diseases associated with Hp. It is concluded that medical science and treatment measures make an important contribution to freeing humanity from Hp infection, but at the present stage, the leading role in this matter is played by the standard of living, public and personal hygiene, and the culture of housing, nutrition and consumption of alcoholic beverages, services, and physical contacts between people
Keywords: Helicobacter pylori; peptic ulcer; gastric cancer; risk factors for infection.